Bahaya Syirik dan Dampak Negatif dalam Kehidupan Modern - Ayudiyah Nabila; Khansa Nadya; M.Raffi Zuvanto; Muhammad Bryan Fahreza; Rafi Laksana Shaum Moon; Wismanto Wismanto; Fitria Mayasari (Pusat Riset dan Inovasi Nasional, 2025)
In modern life, shirk has become one of the things that have a negative impact on individuals and society. The purpose of this study is to find out more about the threats of Allah SWT caused by the practice of shirk in everyday life. This article identifies the root causes of modern shirk, its relevance in social and spiritual contexts and constructive solutions to overcome it using analytical theory and empirical facts. The method used in this study is a descriptive qualitative method, by making the Qur'an, hadith books, books, magazines, articles and leading journals as the main reading sources to be analyzed and concluded into a writing. It is hoped that this method can increase understanding of the complexity of modern shirk and the importance of avoiding its negative impacts. The results of this analysis indicate that to overcome the act of shirk in modern life, appropriate actions and interventions are needed from individuals and society. It was found that the worst consequences of this act of shirk are two kinds of threats from Allah, the first is the threat in (QS. Al Maidah, 5: 72-73); (1) The perpetrator is an infidel, (2) the perpetrator is prohibited from entering heaven, (3) he is guaranteed to go to hell, (4) There will be no intercession in the afterlife. The two threats from Allah in (Q.S. Maryam, 19: 90) 1. The sky is broken, 2. The mountain is erupted, 3. The earth is split (earthquake).